DESCRIPTION OF DEPRESSION LEVELS IN ELDERLY IN GEDANGAN VILLAGE, HARGOMULYO, GEDANGSARI - Erlina Hermawati (Universitas Sahid Surakarta, 2023)
The number of elderly people is increasing with time. Someone who enters the elderly stage will experience many changes both physically and mentally. One of the psychosocial health problems that often occur in the elderly is depression. This study aims to describe the level of depression in the elderly in Gedangan, Hargomulyo, Gedangsari, Gunungkidul. This research is a quantitative research with analytic descriptive design. The sampling technique used in this study was a total sampling of 56 respondents. The instrument used was the GDS (Geriatric Depression Scale Short Form) questionnaire. The results of this study were that the majority of respondents were male, 33 (59%) with an average age of 67.25 years, the marital status of a widow/widower, 29 respondents (52%) and living alone, 29 respondents (52%). The results of measuring depression using the GDS instrument showed normal results in 38 (67.9%), mild depression were 13 respondents (23.2) and moderate depression were 5 respondents (8.9%).